International Travel Patterns and Travel Risks for Stem Cell Transplant Recipients. Issue 1 (17th October 2014) - Mikati, Tarek; Griffin, Kenneth; Lane, Dakotah; Matasar, Matthew; Shah, Monika K.
Abstract : Background: Stem cell transplantation (SCT) is being increasingly utilized for multiple medical illnesses. However, there is limited knowledge about international travel patterns and travel‐related illnesses of stem cell transplant recipients (SCTRs). Methods: An observational cross‐sectional study was conducted among 979 SCTRs at Memorial Sloan Kettering Cancer Center using a previously standardized and validated questionnaire. International travel post SCT, pre‐travel health advice, exposure risks, and travel‐related illnesses were queried. Results: A total of 516 SCTRs completed the survey (55% response rate); of these, 40% were allogeneic SCTRs. A total of 229 (44.3%) respondents reported international travel outside the United States and Canada post SCT. The international travel incidence was 32% [95% confidence interval CI 28–36] within 2 years after SCT. Using multivariable Cox regression analysis, variables significantly associated with international travel within first 2 years after SCT were history of international travel prior to SCT [hazard ratio (HR) = 5.3, 95% CI 2.3–12.0], autologous SCT (HR = 2.6, 95% CI 1.6–2.8), foreign birth (HR = 2.3, 95% CI 1.5–3.3), and high income (HR = 2.0, 95% CI 1.8–3.7). During their first trip, 64 travelers (28%) had traveled to destinations that may have required vaccination or malaria chemoprophylaxis. Only 56% reported seeking pre‐travel health advice. Of those who traveled, 16 travelers (7%) became ill enough to require medical attention during their first trip after SCT. Ill travelers were more likely to have visited high‐risk areas (60 vs 26%, p = 0.005), to have had a longer mean trip duration (24 vs 12 days, p = 0.0002), and to have visited friends and relatives (69 vs 21%, p < 0.0001). Conclusions: International travel was common among SCTRs within 2 years after SCT and was mainly to low‐risk destinations. Although the overall incidence of travel‐related illnesses was low, certain subgroups of travelers were at a significantly higher risk. Pre‐travel health counseling and interventions were suboptimal.